1931
DOI: 10.1104/pp.6.3.549
|View full text |Cite
|
Sign up to set email alerts
|

Respiration Studies of Strawberries

Abstract: In the study of promising new varieties of strawberries, it is desirable to employ some measurement that will give satisfactory evidence of their keeping quality when compared with standard varieties in a district. To this end, HARDY and LOCKLIN (unpublished) have employed a test by means of which the firmness of the fruit is expressed in grams of pressure necessary to force a one-eighth inch plunger through the flesh to a depth of three-sixteentlis of an inch. It was noted, however, that frequently the firmne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1935
1935
1979
1979

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Numerous studies (1,2,3,4,5,6,7,9,10,11,12,13,14,15) have been conducted on postharvest holding of strawberries; however, little research (7) has been reported on the storage quality of machine-harvested strawberries. Acetaldehyde production occurs during postharvest storage of strawberries (12,14,15) when held under high C02 concentrations.…”
mentioning
confidence: 99%
“…Numerous studies (1,2,3,4,5,6,7,9,10,11,12,13,14,15) have been conducted on postharvest holding of strawberries; however, little research (7) has been reported on the storage quality of machine-harvested strawberries. Acetaldehyde production occurs during postharvest storage of strawberries (12,14,15) when held under high C02 concentrations.…”
mentioning
confidence: 99%